Enhancing Posyandu Cadres’ Role in Preventing Non-Communicable Diseases in Gonggang Village, Poncol District, Magetan Regency - Sumasto, Hery; Astuti Setiyani; Wisnu, Nurwening Tyas; Mentari, Mulyananda Dwi; Suhermin (Frontiers in Community Service and Empowerment, 2025)
Non-Communicable Diseases (NCDs) are increasing in prevalence in rural communities and are a serious threat to public health. Posyandu cadres as the frontline of health services at the community level have a strategic role in efforts to prevent and detect NCDs. However, the limited competence and capacity of cadres are often obstacles in optimizing these roles. This community service activity aims to strengthen the role of Posyandu Cadres through increasing competence in the prevention of NCDs in Gonggang Village, Poncol District, Magetan Regency. The method of community service activities is carried out with a participatory approach through training, mentoring, and field practice for Posyandu cadres. The material includes education on risk factors for NCDs, promotion of Clean and Healthy Living Behavior (PHBS), as well as early detection skills and monitoring of citizens' health. The evaluation was carried out using pre-test and post-test knowledge, observation of cadre practices, and feedback from the community. The results of this activity show a significant increase in the knowledge and skills of cadres in recognizing NCD risk factors and conducting health education to the community. Cadres are also able to initiate promotive-preventive activities at the Posyandu, such as healthy lifestyle campaigns, blood pressure measurement, and simple blood sugar monitoring. The support of the community and the village government also strengthens the sustainability of the program. The conclusion of this activity is that strengthening the role of Posyandu Cadres through increasing competence has proven to be effective in supporting the prevention of NCDs at the community level. This model has the potential to be replicated in other regions to support the transformation of primary healthcare